Radiation environment at aviation altitudes and in space - Sihver, L; Ploc, O; Puchalska, M; Ambrožová, I; Kubančák, J; Kyselová, D; Shurshakov, V (Radiation protection dosimetry, 2015)
On the Earth, protection from cosmic radiation is provided by the magnetosphere and the atmosphere, but the radiation exposure increases with increasing altitude. Aircrew and especially space crew members are therefore exposed to an increased level of ionising radiation. Dosimetry onboard aircraft and spacecraft is however complicated by the presence of neutrons and high linear energy transfer particles. Film and thermoluminescent dosimeters, routinely used for ground-based personnel, do not reliably cover the range of particle types and energies found in cosmic radiation. Further, the radiation field onboard aircraft and spacecraft is not constant; its intensity and composition change mainly with altitude, geomagnetic position and solar activity (marginally also with the aircraft/spacecraft type, number of people aboard, amount of fuel etc.). The European Union Council directive 96/29/Euroatom of 1996 specifies that aircrews that could receive dose of >1 mSv y(-1) must be evaluated. The dose evaluation is routinely performed by computer programs, e.g. CARI-6, EPCARD, SIEVERT, PCAire, JISCARD and AVIDOS. Such calculations should however be carefully verified and validated. Measurements of the radiation field in aircraft are thus of a great importance. A promising option is the long-term deployment of active detectors, e.g. silicon spectrometer Liulin, TEPC Hawk and pixel detector Timepix. Outside the Earth's protective atmosphere and magnetosphere, the environment is much harsher than at aviation altitudes. In addition to the exposure to high energetic ionising cosmic radiation, there are microgravity, lack of atmosphere, psychological and psychosocial components etc. The milieu is therefore very unfriendly for any living organism. In case of solar flares, exposures of spacecraft crews may even be lethal. In this paper, long-term measurements of the radiation environment onboard Czech aircraft performed with the Liulin since 2001, as well as measurements and simulations of dose rates on and outside the International Space Station were presented. The measured and simulated results are discussed in the context of health impact.
Keywords: Atmosphere; pracovní expozice; Radiation Dosage; Software; Humans; kosmické záření; Space Flight; Occupational Exposure; Phantoms, Imaging; Radiation Exposure; fantomy radiodiagnostické; sluneční aktivita; lineární přenos energie; letadla; atmosféra; Linear Energy Transfer; software; Solar Activity; radiační expozice; Aerospace Medicine; letecké a kosmické lékařství; lidé; Cosmic Radiation; neutrony; Neutrons; Radiometry; dávka záření; kosmický let; Spacecraft; radiometrie; kosmická loď; Aircraft